2023
DOI: 10.6004/jnccn.2022.7068
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Patients With Limited English Proficiency in Gynecologic Oncology Clinical Trials

Abstract: Background: Significant disparities exist in recruitment of minorities to clinical trials, with much of the prior literature focused on race/ethnicity only. Limited English proficiency (LEP) is a known barrier in healthcare that may also drive disparities in trial enrollment. We sought to determine participation rates in gynecologic oncology trials among patients with LEP and to explore barriers to their participation. Methods: In a retrospective cohort study, electronic health record data from >2,700 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…In a retrospective cohort study based on reviews of electronic health record data from 2,793 patients with gynecologic cancers, the authors found a 71% reduction in likelihood of trial participation for those with LEP (2.2% participation) compared with fluent English speakers (7.5%). 6 This finding was robust to covariate adjustment for known confounders of ethnicity and insurance, and the observed trends were consistent across levels of demographic, socioeconomic, and other key variables, further supporting the idea that LEP is independently related to trial participation. Importantly, to underscore the causal relationship, the authors also surveyed gynecologic research staff and providers, who indicated that the main reasons for limited participation of patients with LEP were unavailability of translated consent forms and increased time needed to enroll patients.…”
supporting
confidence: 54%
See 3 more Smart Citations
“…In a retrospective cohort study based on reviews of electronic health record data from 2,793 patients with gynecologic cancers, the authors found a 71% reduction in likelihood of trial participation for those with LEP (2.2% participation) compared with fluent English speakers (7.5%). 6 This finding was robust to covariate adjustment for known confounders of ethnicity and insurance, and the observed trends were consistent across levels of demographic, socioeconomic, and other key variables, further supporting the idea that LEP is independently related to trial participation. Importantly, to underscore the causal relationship, the authors also surveyed gynecologic research staff and providers, who indicated that the main reasons for limited participation of patients with LEP were unavailability of translated consent forms and increased time needed to enroll patients.…”
supporting
confidence: 54%
“…4 Indeed, in a recent study, when patients were offered the opportunity to participate in a trial that was available and for which they were clinically eligible, they agreed to do so at astounding rates; .50% of patients of all racial and ethnic backgrounds indicated they wished to enroll. 5 With this as background, the findings from Jorge et al, 6 reported elsewhere in this issue, represent an important contribution to the literature. The authors investigated the role of limited English proficiency (LEP) as a reason for nonparticipation in clinical trials.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Cancer patients with limited English proficiency (LEP) encounter similar challenges to accessing and participating in cancer clinical trials [ 66 ]. In a retrospective cohort study of patients with gynecologic cancers, Jorge et al [ 67 ] found that even after adjusting for ethnicity and insurance status, patients with LEP had 66% lower odds of participating in clinical trials than fluent English speakers. In addition, a survey of gynecologic research staff and providers identified the most significant barriers to research participation for patients with LEP to be the lack of translated consent forms and increased time needed to enroll patients with LEP [ 67 ].…”
Section: Barriers To Accessing Cancer Clinical Trialmentioning
confidence: 99%